Emotional Motivation in industrial products design and its reflection on the consumer (Al-Academy, 2023)
This research discusses the subject of emotional stimulation factors through the stages of product design interaction with the consumer and what they reflect in the formation of a self-consideration of the design in his emotional memory regarding the specific brand through the following question (What is the emotional stimulus in the design of certain products and its reflection on the consumer during the processes of receiving and using it?), The importance of the research comes in the connection of design elements with many sensory factors used and motivating to attract the consumer to the acquisition of a specific design and the demand for its experience, the study aims Detection and access to emotional stimulation in the design of the industrial product to develop the design process, and were defined by the designs of BRAUN products for home use in Baghdad markets (limited edition) for the year 2021 and its reflection on consumers. The theoretical framework dealt with the concept of emotions in the design of industrial products and their importance in motivating the acquisition of products, preference for appearance, performance, value, stages of motivation in interaction with the product, and their impact on gender differences, emotional age, value formation, and mood towards the product.The researcher relied on a questionnaire with specific axes to analyze the sample models and access the research results and conclusions, the most important of which are:- The result of the stimulus in the stages of receiving and using is reflected in the creation of value for the product.- The value and mood towards the design in case the product is already known to the consumer (a new version or a second model) leads the consumer and determines his interaction through feelings of receiving and feelings of use it.